Modul Pembelajaran Mata Kuliah PLC Menggunakan Pendekatan Logika Program Berbasis Software Automation Studio untuk Meningkatkan Kemampuan Pemahaman Logika Program Mahasiswa - Hasan Hasan; Irawan Suharto; Rianda Rianda (Politeknik Negeri Pontianak, 2018)
The purpose of this research is to make the learning module of PLC courses for the Theory and Practicum activities. This learning module uses logical approach based on Software Automation Studio as simulation module of logic flow, both logic in hardware wirring and logic of software program based on ladder diagram. For PLC hardware as a learning module created, use PLC Master-K Type K7M-DT30U. This module is made because of the low logic of basic understanding of students in PLC courses both in theory and practice in the final result of the course value. The object of this research is the students of Semester V of Electrical Engineering Program of Polnep as many as 35 people in the PLC course and the subjects of the Practicum of Control System 1 (Basic PLC). The result of the research is a set of basic PLC practicum / module tools using Master-K Type K7M-DT30U PLC and guide module guide using Automation Studio software as simulation tool. From the final evaluation result, it is found that there is an increase of students' logic in making PLC program and the improvement of ability in practicum activity. This is evidenced by the average grade for the 2 batches of the school year. For of class of 2014 the average value of PLC for academic year 2016/2017 amounted to 58.19 and practice control system 1 75.05. Now that the app is used for the 2015 generation, the academic year 2017/2018 increases to 70.26 for PLC and 79.45 for the lab.